Influence of anchorage length of composite fabrics and bonded surface on the strengthened short reinforced concrete corbel by bonding CFRF. Issue 12 (14th October 2020) - Ivanova, Ivelina; Assih, Jules; Dontchev, Dimitar
Abstract: This article presents an experimental study of the mechanical behavior of strengthened short reinforced concrete (RC) corbel by externally glued Carbon Fibre Reinforced Fabrics (CFRF). Six reinforced concrete corbels were fabricated. One of them was the reference specimen without strengthening and the other five corbels were strengthened with different configuration schemes of CFRF. The experimental test performed consists in three-point monotonous flexural loading until failure. The local deformations on different points in the constituent materials (steel, concrete and CFRF) were studied using extensometer technique based on electrical strain gauge system. The development of local deformations in the constituent materials depending on the external load was plotted and analyzed. The test results according to different strengthening schemes are compared and analyzed. The obtained results indicated that the proposed CFRF strengthening technique has potential in improving the ultimate load up to 80% of carrying capacity. The results show well the effect the anchored length has on the ultimate load and on the behavior of the strengthened RC corbels. The mechanisms of cracks development and the different modes of failures (CFRF debonding, CFRF failure, and concrete crushing (shear and bending cracking)) are presented and discussed.